2022
DOI: 10.3389/fimmu.2021.764949
|View full text |Cite
|
Sign up to set email alerts
|

CD8+ T-Cell Epitope Variations Suggest a Potential Antigen HLA-A2 Binding Deficiency for Spike Protein of SARS-CoV-2

Abstract: We identified SARS-CoV-2 specific antigen epitopes by HLA-A2 binding affinity analysis and characterized their ability to activate T cells. As the pandemic continues, variations in SARS-CoV-2 virus strains have been found in many countries. In this study, we directly assess the immune response to SARS-CoV-2 epitope variants. We first predicted potential HLA-A*02:01-restricted CD8+ T-cell epitopes of SARS-CoV-2. Using the T2 cell model, HLA-A*02:01-restricted T-cell epitopes were screened for their binding affi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 28 publications
2
11
0
Order By: Relevance
“…Thus, we predicted the complete absence of T-cell immunity evasion at the level of the whole virus. This agrees with the recent findings by Xiao and Qiu with co-authors: while several peptides lost binding ability to HLA-A*02 because of mutations, overall levels of T-cell immunity were not strongly decreased ( Qiu et al, 2021 ; Xiao et al, 2022 ). When the analysis was limited to the Spike protein, remarkably higher number of alleles was identified: eight alleles showed enhanced ability of Omicron/Delta peptide presentation, while four remaining alleles showed significant decrease in the number of tight binders.…”
Section: Discussionsupporting
confidence: 93%
“…Thus, we predicted the complete absence of T-cell immunity evasion at the level of the whole virus. This agrees with the recent findings by Xiao and Qiu with co-authors: while several peptides lost binding ability to HLA-A*02 because of mutations, overall levels of T-cell immunity were not strongly decreased ( Qiu et al, 2021 ; Xiao et al, 2022 ). When the analysis was limited to the Spike protein, remarkably higher number of alleles was identified: eight alleles showed enhanced ability of Omicron/Delta peptide presentation, while four remaining alleles showed significant decrease in the number of tight binders.…”
Section: Discussionsupporting
confidence: 93%
“…Thus, hypothetical new CD8 + T-cell epitopes would be loaded onto corresponding HLA-I molecules and trigger new and specific T-cell activation for a completedelayed-VOC clearance. Studies by Qiu et al (75) and Elisa Guo and Hailong Guo (74) demonstrated the possibility of new CD8 + T-cell epitopes from mutated epitopes of SARS-CoV-2, with the ability to increase T-cell activation marker CD69 and CD137 and induce low titer CD8 + T-cell response specific to the mutants, but then, no more specific to the WT SARS-CoV-2. Future studies need to assess the possibility of new epitopes from SARS-CoV-2 VOC infections and their effectiveness in the clearance of SARS-CoV-2 VOCs.…”
Section: Discussion and Concluding Remarksmentioning
confidence: 99%
“…However, this-early-immunity effectiveness might be mainly attributed to memory CD4 + T-cells and, to a lesser extent, to memory B-cells and antibodies, but probably not to memory CD8 + T-cells. This is because, as described in Section 4, mutated epitopes carried by VOCs may no longer be recognized by preexisting CD8 + T-cell immunity, as mutations in SARS-CoV-2 negatively affect mainly CD8 + T-cell epitopes that are more vulnerable (62,75), but not CD4 + T-cell epitopes for which the same preexisting SARS-CoV-2 immune response still retains efficacy against mutants and may appropriately reduce VOC infection-associated severity (72). Consequently, we suggested that the clearance of VOC infections later on without intensive care admission could be possibly attributed to the development of new CD8 + T-cell epitopes specific to variants, together with the conserved preexisting CD4 + T-cell, which aligns with the global pattern of the COVID-19 pandemic [surges in new cases followed by prevalence declines months later (https:// covid19.who.int/)].…”
Section: Discussion and Concluding Remarksmentioning
confidence: 99%
See 2 more Smart Citations